When Fiction Becomes History: The Morphology of Context in the Short Stories of Bridget O’Connor (ES Review. Spanish Journal of English Studies, 2025)
Taking as its theoretical starting-point Bergson’s notion of subjective time and as a practical exemplar Proust’s In Search of Lost Time, this article contends that fiction has the capacity to morph historical context, thereby making it phenomenologically present to readers. As a formal contrast to Proust’s immense novel, Bridget O’Connor’s short stories are analyzed to show how even short fiction can give shape to context, in this case through aspects of style and characterization. As a result, conventional distinctions between history and fiction are elided, which in turn challenges conventional definitions of historical fiction.
Keywords: Bridget O’Connor; Marcel Proust; context; morphology; history; fiction